Data Governance and Privacy in Sulu, Philippines: Building Trust and Ensuring Accountability in Digital Public Service Delivery - Datu Ansaruddin K. Kiram; Mharcelyn M. Kiram; Jul-Asri A. Hadjibun; Merhana Taraji (HM Publisher, 2025)
The province of Sulu in the Philippines faces unique challenges in implementing digital governance initiatives due to its geographical remoteness, socio-economic disparities, and security concerns. This study examines the critical issue of data governance and privacy in Sulu's digital public service delivery, focusing on building trust and ensuring accountability. This research employed a mixed-methods approach. Quantitative data was collected through a survey of 300 residents of Sulu involved in accessing digital public services. Qualitative data was gathered through semi-structured interviews with 20 key informants, including local government officials, civil society representatives, and technology experts. The study analyzed existing policies and frameworks related to data governance and privacy in the Philippines and compared them with international best practices. The findings revealed a significant gap between policy aspirations and the reality on the ground. While national policies emphasize data privacy and security, awareness and implementation at the local level in Sulu remain limited. The study identified challenges such as lack of digital literacy, inadequate infrastructure, and concerns about data misuse. However, it also highlighted opportunities for leveraging digital technologies to improve transparency, accountability, and citizen participation in public service delivery. In conclusion, this study provides valuable insights for policymakers and practitioners working on digital governance in Sulu and other similar contexts. It emphasizes the need for context-specific strategies that prioritize community engagement, capacity building, and robust oversight mechanisms to ensure responsible and ethical data governance.